Toxicity Evaluation and Controlled-Release of Curcumin-Loaded Amphiphilic Poly-N-vinylpyrrolidone Nanoparticles: In Vitro and In Vivo Models - Anna L. Luss; Dmitry V. Bagrov; Anne V. Yagolovich; Ekaterina V. Kukovyakina; Irina I. Khan; Vadim S. Pokrovsky; Maria V. Shestovskaya; Marine E. Gasparian; Dmitry A. Dolgikh; Andrey N. Kuskov (MDPI AG, 2023)
Curcumin attracts huge attention because of its biological properties: it is antiproliferative, antioxidant, anti-inflammatory, immunomodulatory and so on. However, its usage has been limited by poor water solubility and low bioavailability. Herein, to solve these problems, we developed curcumin-loaded nanoparticles based on end-capped amphiphilic poly(N-vinylpyrrolidone). Nanoparticles were obtained using the solvent evaporation method and were characterized by dynamic and electrophoretic light scattering, transmission electron (TEM) and atomic force (AFM) microscopy. The average particle size was 200 nm, and the ζ-potential was −4 mV. Curcumin-release studies showed that nanoparticles are stable in aqueous solutions. An in vitro release study showed prolonged action in gastric, intestinal and colonic fluids, consistently, and in PBS. In vitro studies on epidermoid carcinoma and human embryonic kidney cells showed that the cells absorbed more curcumin in nanoparticles compared to free curcumin. Nanoparticles are safe for healthy cells and show high cytotoxicity for glioblastoma cells in cytotoxicity studies in vitro. The median lethal dose was determined in an acute toxicity assay on zebrafish and was 23 μM. Overall, the curcumin-loaded nanoparticles seem promising for cancer treatment.